Fixed Point Theorems in Complete Cone Metric Spaces over Banach Algebras. (5th August 2018) - Cho, Seong-Hoon
Abstract : The notion of C-class functions in Banach algebras is introduced. By using such concept, a new fixed point theorem is established. An example to illustrate main theorem is given. Finally, applications of our main result to cyclic mappings and weak contraction type mappings are given.